Un double compromis. Enjeux et débats relatifs à l'enseignement universitaire en Belgique au XIXe siècle - Dhondt, Pieter (Academia Press, 2006)
This book reveals the history of discussions regarding university education in Belgium, from the abolishment of the old university of Leuven in 1797 to the promulgation of the laws on higher education in 1890 and 1891. Different issues pass the revue, such as the number and location of the universities, the entrance conditions, the educational programme and methods, the organisation of the examination system, the transformation of the university - from a vocational school to a research institution -, the training of future professors and the admission of women to the university. The general debates are systematically confronted with practical developments within the faculties of arts and medicine. A double compromise characterised both the debates and the practical realisations: between what was generally considered the French model and the German university system, and between the internal and external freedom of the universities.